Packaging of Mason-Pfizer monkey virus (MPMV) genomic RNA depends upon conserved long-range interactions (LRIs) between U5 and gag sequences - Kalloush, Rawan M. (RNA, 2016)
MPMV has great potential for development as a vector for gene therapy. In this respect, precisely defining the sequences and structural motifs that are important for dimerization and packaging of its genomic RNA (gRNA) are of utmost importance. A distinguishing feature of the MPMV gRNA packaging signal is two phylogenetically conserved long-range interactions (LRIs) between U5 and gag complementary sequences, LRI-I and LRI-II. To test their biological significance in the MPMV life cycle, we introduced mutations into these structural motifs and tested their effects on MPMV gRNA packaging and propagation. Furthermore, we probed the structure of key mutants using SHAPE (selective 2′hydroxyl acylation analyzed by primer extension). Disrupting base-pairing of the LRIs affected gRNA packaging and propagation, demonstrating their significance to the MPMV life cycle. A double mutant restoring a heterologous LRI-I was fully functional, whereas a similar LRI-II mutant failed to restore gRNA packaging and propagation. These results demonstrate that while LRI-I acts at the structural level, maintaining base-pairing is not sufficient for LRI-II function. In addition, in vitro RNA dimerization assays indicated that the loss of RNA packaging in LRI mutants could not be attributed to the defects in dimerization. Our findings suggest that U5-gag LRIs play an important architectural role in maintaining the structure of the 5′ region of the MPMV gRNA, expanding the crucial role of LRIs to the nonlentiviral group of retroviruses.